Nitrogen, phosphorus and sulfur three-element doped carbon-coated lithium iron phosphate positive electrode material and preparation method thereof

Through the carbon coating technology of nitrogen, phosphorus and sulfur three elements doped with carbon coating technology, the problem of poor conductivity of lithium iron phosphate positive electrode material is solved, and better electrochemical performance and rate performance are achieved, which significantly improves the overall performance of the material.

CN116514087BActive Publication Date: 2025-01-14HUADING GUOLIAN SICHUAN BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310059345.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-20
Publication Date
2025-01-14
Estimated Expiration
2043-01-20

AI Technical Summary

Technical Problem

The current lithium iron phosphate positive electrode materials have poor conductivity, resulting in poor rate performance and low temperature performance. The thickness of existing carbon coating materials is difficult to control, and too little or too many doped metal ions will affect the performance.

Method used

Preparation method of lithium iron phosphate positive electrode material coated with nitrogen, phosphorus and sulfur trielement doped carbon coated, by adding tripolymer phosphazene chloride and 4,4'-sulfonyl diphenol to the lithium iron phosphate precursor, stirring and carbonization The treatment is combined with a high mixer to form a 5-15nm-thick, nitrogen, phosphorus and sulfur tri-element doped carbon layer to improve the conductivity of the material.

Benefits of technology

It significantly improves the conductive and electrochemical properties of the material, is better than sucrose-coated materials, enhances the lithium ion transmission rate and material stability, and improves the rate performance and low-temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116514087B_ABST
    Figure CN116514087B_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material. The method comprises the following steps: placing a lithium iron phosphate precursor into a solution, stirring and adding tripolyphosphazene chloride and 4,4'-sulfonyl diphenol, stirring, adding triethylamine, continuously stirring, washing, and drying to obtain a lithium iron phosphate precursor material coated with PZS (polycyclotriphosphazene-co-4,4'-sulfonyl diphenol); placing the coated material in a tubular furnace for sintering to complete carbonization of PZS; placing the carbonized lithium iron phosphate precursor and a lithium source in a high-speed mixer for mixing, wherein the lithium iron phosphate precursor can provide better electrical conductivity, and the doping benefits of nitrogen, phosphorus and sulfur for lithium iron phosphate enable the material to provide excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium iron phosphate positive electrode materials for lithium ion batteries, and specifically relates to a nitrogen, phosphorus and sulfur three-element doped carbon-coated lithium iron phosphate positive electrode material for lithium ion batteries and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have gradually replaced lead-acid batteries and have been widely used due to their high theoretical specific capacity, safety, and no memory effect. Lithium-ion batteries are mainly composed of four main materials, namely positive electrode materials, negative electrode materials, diaphragms, and electrolytes, as well as auxiliary materials. Among them, the positive electrode material is mainly a ternary positive electrode material or lithium iron phosphate. Compared with ternary materials, lithium iron phosphate does not contain precious metals, the raw materials are non-toxic and cheap, and the olivine structure is more stable than the ternary layered structure. Therefore, it has better cycle performance and safety performance, and is expected to be widely used in the field of energy storage. However, lithium iron phosphate has poor conductivity and large particle size, and the lithium ion transmission path is long, so the rate performance and low temperature performance are poor. Therefore, it is necessary to modify the existing lithium iron phosphate to meet the use requirements.

[0003] The first existing technology is to improve the conductivity of the positive electrode material and the migration rate of lithium ions by carbon coating the lithium iron phosphate positive electrode material, thereby improving the conductivity of the overall material; in this method, the existing coating material is mostly sucrose, the process is simple, but the thickness of the coated carbon cannot be controlled; in fact, if the carbon layer is too thick, the overall gram capacity of the material will be reduced, and if the carbon layer is too thin, the improvement of the conductivity of the material is very limited and the coating is uneven. In order to improve the intrinsic conductivity of the material, the second existing technology is to increase the deintercalation rate of lithium ions by doping metal ions such as Ti4+, Co2+, Zn2+, and Mn2+; however, too little doping has little effect on the performance of the material, and if the doping amount is large, it will in turn affect the performance of the material.

[0004] The object of the present invention is to provide a nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material and a preparation method thereof, so that the overall electrical conductivity of the material can be improved. Summary of the invention

[0005] At present, no carbon coating that can provide nitrogen, phosphorus and sulfur doping has been found. The present invention provides a nitrogen, phosphorus and sulfur doped carbon coated lithium iron phosphate positive electrode material and a preparation method thereof, which aims to coat the positive electrode material, isolate the electrolyte, and improve the conductivity of the overall material.

[0006] The invention relates to a preparation method of a nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material. The method comprises the following steps: putting a lithium iron phosphate precursor into a solution, stirring and adding tripolyphosphazene chloride and 4,4'-sulfonyl diphenol, stirring, adding triethylamine, continuously stirring, washing, and drying to obtain a lithium iron phosphate precursor material coated with PZS (polycyclotriphosphazene-co-4,4'-sulfonyl diphenol); placing the coated material in a tubular furnace for sintering to complete carbonization of PZS; placing the carbonized lithium iron phosphate precursor and a lithium source in a high-speed mixer for mixing, placing the mixed sample in a tubular furnace for sintering to obtain the obtained material.

[0007] Furthermore, the lithium iron phosphate precursor can be iron phosphate, iron nitrate, or iron oxalate; the lithium source is lithium carbonate or lithium hydroxide; the dosage ratio of tripolyphosphazene chloride to 4,4'-sulfonyl diphenol and triethylamine is tripolyphosphazene chloride (150-250 g): 4,4'-sulfonyl diphenol (200-300 g): triethylamine (1-5 L); the coated sample is placed in a tubular furnace, the protective gas is one of argon, nitrogen, and oxygen, the heating rate is 2-10°C / min, the sintering temperature is 500-800°C, and the insulation time is 1-5h to complete the carbonization of PZS; the molar ratio of the carbonized lithium iron phosphate precursor to the lithium source is 1.0-1.08; the mixing parameters of the high-speed mixer are: the low speed of the high-speed mixer is 60-420 r / min, the rotation time is 2-20min; the high speed is 600-900 r / min n, the rotation time is 5-35min; the protective gas in the tubular furnace is one of oxygen, air, nitrogen and argon; the sintering temperature is 800-950℃, the heating rate is 2-9℃ / min, and the insulation time is 1-15h.

[0008] The present invention also relates to a nitrogen, phosphorus and sulfur three-element doped carbon-coated lithium iron phosphate positive electrode material obtained by the above preparation method; the PZS obtained by the preparation method has a thickness of 5-15nm.

[0009] The present invention also relates to the application of the nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material in button cells, which is prepared by mixing and coating the nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material with PVDF and SP.

[0010] Furthermore, the mass ratio of the nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material to PVDF and SP is preferably 9-10:0.1-0.5:0.1-0.5; and the button battery is a CR2302 button battery.

[0011] For example, the present invention can be implemented by the following technical solutions:

[0012] The lithium iron phosphate precursor (which can be commercially available, including but not limited to iron phosphate, iron nitrate, iron oxalate, etc.) is placed in a methanol solution, a certain amount of tripolyphosphazene chloride and 4,4'-sulfonyl diphenol (10-300g) is added under continuous stirring, and after stirring for 1-30min, triethylamine is added, and continuous stirring is performed for 8-25h. After washing, the mixture is placed in a vacuum drying oven and dried for 1-15h to complete the PZS (polycyclotriphosphazene-co-4,4'-sulfonyl diphenol)-coated lithium iron phosphate precursor material. The coated sample is placed in a tubular furnace, the protective gas is one of argon, nitrogen, and oxygen, the heating rate is 2-10℃ / min, the sintering temperature is 500-800℃, and the holding time is 1-5h to complete the carbonization of PZS. The obtained lithium iron phosphate precursor material and (which may be commercially available) lithium source (such as lithium carbonate or lithium hydroxide) are mixed in a high-speed mixer at a molar ratio of 1.0-1.08; the mixing parameters of the high-speed mixer are: the low speed of the high-speed mixer is 60-420r / min, the rotation time is 2-20min; the high speed is 600-900r / min, and the rotation time is 5-35min. The mixed sample is placed in a tubular furnace for sintering, wherein the protective gas is one of oxygen, air, nitrogen, and argon, the sintering temperature is 800-950℃, the heating rate is 2-9℃ / min, and the holding time is 1-15h. The sintered sample is LFP@PZS. The finished product is mixed and coated with PVDF and SP in a ratio of 9:0.5:0.5, 9.5:0.2:0.3 or 9.8:0.1:0.1, and finally made into a CR2302 button battery for testing, with a test voltage of 2.7-3.65V.

[0013] Beneficial effects of the present invention:

[0014] Compared with sucrose coating, the carbon of the PZS (polycyclotriphosphazene-co-4,4'-sulfonyldiphenol) coated lithium iron phosphate precursor material of the present invention can provide better conductivity, and the doping effect of nitrogen, phosphorus and sulfur on lithium iron phosphate enables the material to provide excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0016] Figure 1 It is a comparison chart of the first charge and discharge of the two materials of the embodiment and the comparative example. DETAILED DESCRIPTION

[0017] To facilitate understanding of the present invention, various exemplary embodiments of the present invention are now described in detail. This detailed description should not be regarded as a specific limitation of the present invention, but should be understood as a more detailed description of certain aspects, features and embodiments of the present invention.

[0018] Example 1

[0019] Weigh 200g of commercially available iron phosphate precursor and disperse it in a methanol solution and stir it. Then add it dropwise to a 40L methanol solution containing 200g of tripolyphosphazene chloride and 226g of 4,4'-sulfonyldiphenol. After stirring for 5min, add 2L of triethylamine and continue stirring for 18h. After the reaction is completed, the precipitate is filtered and placed in a vacuum drying oven at 80℃ for 5h. The dried sample is placed in a tubular furnace with argon as the protective gas, sintering temperature of 700℃, heating rate of 6℃ / min, and insulation time of 3h to complete the carbonization of PZS. The carbonized iron phosphate precursor and 96.72g of lithium hydroxide are placed in a high-speed mixer and rotated at a low speed of 200r / min for 3min and a high speed of 620r / min for 13min to complete the mixing. The mixed materials were placed in a tube furnace, liquid oxygen was introduced before sintering, the temperature was raised to 900°C at a rate of 6°C / min, and the temperature was kept for 10 hours, and then the sintered sample was taken out, which was LFP@PZS. The finished product was mixed and coated with PVDF and SP in a ratio of 9:0.5:0.5, and finally made into CR2302 button batteries for testing, with a test voltage of 2.7-3.65V.

[0020] Comparative Example 1

[0021] The same 200g iron phosphate precursor and 96.72g lithium hydroxide were placed in a high mixer, rotated at a low speed of 200r / min for 3min, and a high speed of 620r / min for 13min to complete the mixing. The mixed material was placed in a tubular furnace, liquid oxygen was introduced before sintering, the heating rate was 6℃ / min, raised to 900℃, and kept warm for 10h, then the sintered sample was taken out, and then 3% of sucrose was added and mixed with lithium iron phosphate ball mill for 10h, placed in a tubular furnace, argon atmosphere, sintering temperature 700℃, insulation time 4h, complete the carbonization of sucrose, recorded as LFP@C. The finished product was mixed and coated with PVDF and SP in a ratio of 9:0.5:0.5, and finally made into a CR2302 button battery for testing, with a test voltage of 2.7-3.65V.

[0022] Table 1. Comparison of rate performance of two materials

[0023] 0.1C discharge 0.2C discharge 0.33C discharge 0.5C discharge 1C discharge LFP@PZS 164.95mAh / g 161.77mAh / g 157.13mAh / g 153.79mAh / g 144.52mAh / g LFP@C 161.22mAh / g 160.45mAh / g 155.09mAh / g 152.77mAh / g 143.35mAh / g

[0024] Table 1 is a comparison of the rate performance of the two materials of the embodiment and the comparative example. It can be seen that the performance data of the present invention are superior to those of the comparative example. Figure 1 The first charge and discharge comparison of the two materials is shown in the figure. It can be seen that the first charge specific capacity of LFP@PZS and LFP@C are 163.1mAh / g and 162.9mAh / g, respectively, and the first discharge specific capacity is 161.8mAh / g and 155.7mAh / g, respectively, and the corresponding first coulombic efficiency is 96.9% and 96.7%; at the same time, Table 1 compares the rate performance of the two materials. At different rates, the performance of LFP@PZS is better than that of LFP@C. LFP@PZS is better than LFP@C in both the first discharge specific capacity and coulombic efficiency, which is mainly due to the influence of the coated carbon layer. Compared with undoped sucrose carbon, nitrogen, phosphorus and sulfur doped carbon can provide better performance.

[0025] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a nitrogen, phosphorus and sulfur three-element doped carbon-coated lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: The lithium iron phosphate precursor is placed in a solution, stirred and tripolyphosphazene chloride and 4, 4'-sulfonyldiphenol are added, and then triethylamine is added, and stirring is continued. After washing, the solution is dried to obtain a lithium iron phosphate precursor material coated with PZS (polycyclotriphosphazene-co-4,4'-sulfonyldiphenol); the coated material is sintered in a tubular furnace to complete the carbonization of PZS; the carbonized lithium iron phosphate precursor and the lithium source are placed in a high-speed mixer for mixing, and the mixed sample is placed in a tubular furnace for sintering to obtain the product.

2. The method for preparing a nitrogen, phosphorus and sulfur three-element doped carbon-coated lithium iron phosphate positive electrode material as claimed in claim 1, characterized in that: The lithium iron phosphate precursor may be iron phosphate, iron nitrate, or iron oxalate; and the lithium source may be lithium carbonate or lithium hydroxide.

3. A method for preparing a nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material according to any one of claims 1 and 2, further characterized in that the ratio of tripolyphosphazene chloride to 4, 4'-sulfonyl diphenol and triethylamine is tripolyphosphazene chloride (150-250g): 4, 4'-sulfonyl diphenol (200-300g): triethylamine (1-5L); the PZS carbonization process is a protective gas in a tubular furnace of one of oxygen, air, nitrogen and argon; the sintering temperature is 500-800°C, the heating rate is 2-10°C / min, and the holding time is 1-5h; the molar ratio of the carbonized lithium iron phosphate precursor to the lithium source is 1.0-1.

08.

4. The method for preparing a nitrogen, phosphorus and sulfur three-element doped carbon-coated lithium iron phosphate positive electrode material as claimed in claim 1, characterized in that: The mixing parameters of the high-speed mixer are: the low speed of the high-speed mixer is 60-420r / min, and the rotation time is 2-20min; the high speed is 600-900r / min, and the rotation time is 5-35min.

5. The method for preparing a nitrogen, phosphorus and sulfur three-element doped carbon-coated lithium iron phosphate positive electrode material as claimed in claim 1, characterized in that: The protective gas in the tubular furnace is one of oxygen, air, nitrogen and argon; the sintering temperature is 800-950°C, the heating rate is 2-9°C / min, and the holding time is 1-15h.

6. The nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material obtained by the preparation method according to any one of claims 1 to 5.

7. Use of the nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material obtained by the preparation method according to any one of claims 1 to 5 or the nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material according to claim 6 in button batteries, which is prepared by mixing and coating the nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material with PVDF and SP.

8. Application of the nitrogen, phosphorus and sulfur three-element doped carbon-coated lithium iron phosphate positive electrode material in button batteries as claimed in claim 7, wherein: The mass ratio of nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material to PVDF and SP is preferably 9-10:0.1-0.5:0.1-0.

5.

9. Use of the nitrogen, phosphorus and sulfur doped carbon-coated lithium iron phosphate positive electrode material as claimed in claim 7 or 8 in a button battery, further, the button battery is a CR2302 button battery.

Citation Information

Patent Citations

  • Anion and cation doped carbon-coated lithium iron phosphate cathode material and preparation method thereof

    CN103887513A

  • Preparation method for sulfur-doped and carbon-coated lithium iron phosphate positive electrode material co-doped with strontium and manganese

    CN107195873A